2017
DOI: 10.21873/anticanres.11725
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of ATP and Adenosine on Cholangiocarcinoma Cell Proliferation and Motility

Abstract: ATP and adenosine had anti-proliferative and anti-motility effects in CCA cells, while there was a smaller effect on normal cholangiocytes. These data indicate the potential use of ATP and odenosine as a novel therapy for CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Adenosine has been found to both inhibit and stimulate the proliferation of cancer cells [26]. As in our study, an overwhelming number of publications describe its antiproliferative activity, including in prostate cancer [30], ovarian cancer [31], cholangiocarcinoma [32] and AML [28,29]. ATP and ADP (in the low micromolar range) are competitive inhibitors of 5 -nucleotidase that hydrolyze AMP to adenosine and inorganic phosphate.…”
Section: Discussionsupporting
confidence: 65%
“…Adenosine has been found to both inhibit and stimulate the proliferation of cancer cells [26]. As in our study, an overwhelming number of publications describe its antiproliferative activity, including in prostate cancer [30], ovarian cancer [31], cholangiocarcinoma [32] and AML [28,29]. ATP and ADP (in the low micromolar range) are competitive inhibitors of 5 -nucleotidase that hydrolyze AMP to adenosine and inorganic phosphate.…”
Section: Discussionsupporting
confidence: 65%
“…We further investigated the potential molecular pathways underlying this inhibition and have demonstrated that adenosine inhibited CCA cells in a receptor-independent mechanism. Some of these cell lines including HuCCA-1, RMCCA-1 and MMNK-1 were reported to not express adenosine receptor genes, [17] while other cell lines expressed some adenosine receptor genes ( Figure S1 and Table S1). Furthermore, expression of ENPP1-3 and ENTPD1-3 (CD39 family), which convert ATP to AMP [43,44], was ubiquitous.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α levels are significantly elevated in cholangiocarcinoma cell lines compared to normal biliary cells and HIF-1α is important for cholangiocarcinoma cell line proliferation, migration, and invasion ( Yu et al, 2020 ). ATP and adenosine have been shown to have anti-proliferative and anti-motility effects ( Lertsuwan and Ruchirawat, 2017 ) in experiments conducted using cholangiocarcinoma cell (CCA) lines. Purinergic receptor expression levels in CCA cell lines were analyzed using qPCR and P2 receptors were expressed in CCA cell lines and in immortalized cholangiocytes, but in this study, adenosine receptors were not identified.…”
Section: Bile Duct Cancermentioning
confidence: 99%